weighted blankets, sensory-based interventions, autism spectrum disorder - Teresa A. May-Benson; Sarah Schoen; Alison Teasdale; Jane Koomar (Open Journal of Occupational Therapy, 2021)
Background: Goal Attainment Scaling (GAS) is advocated as a meaningful outcome measure for parents and clinicians using an Ayres Sensory Integration® Intervention (ASI) approach. Although used in several treatment effectiveness studies, reliability of therapist goal writing and scoring has not been established in this area.